Perbandingan Self-Efficacy Ditinjau dari Status Pemain Esport (Profesional dan Amatir) - Dida Kusumah; Yati Ruhayati; Mohammad Zaky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the differences in self-efficacy levels between professional and amateur esports players. A quantitative approach with a comparative research design was employed. The study involved 100 esports players, consisting of both professional and amateur players, who were selected using a purposive sampling technique. Data were collected using the General Self-Efficacy Scale (GSES) developed by Schwarzer and Jerusalem (1995). The data were analyzed using descriptive statistics and an Independent Samples t-test to examine differences in self-efficacy between the two groups. The findings revealed no significant difference in self-efficacy levels between professional and amateur esports players. These results indicate that player status is not a direct factor distinguishing individuals' confidence in their ability to cope with challenges and accomplish tasks within the esports context. In conclusion, self-efficacy can be developed through various factors, including playing experience, social support, and the learning processes acquired by players. Therefore, the development of psychological aspects should receive greater attention in esports training and development programs at all levels of competition to optimize player performance and long-term development. Keywords: Esports, Amateur Players, Professional Players, Self-Efficacy